Information transmission within federal fiscal architectures: theory and evidence - Dreher, Axel; Gehring, Kai; Kotsogiannēs, Chrēstos; Marchesi, Silvia (CESifo working papers, 2013)
This paper explores the role of information transmission and misaligned interests across levels of government in explaining variation in the degree of decentralization across countries. Within a two-sided incomplete information principal-agent framework, it analyzes two alternative policy-decision schemes - "decentralization" and "centralization" - when "knowledge" consists of unverifiable information and the quality of communication depends on the conflict of interests between the government levels. It is shown that, depending on which level of policy decision-making controls the degree of decentralization, the extent of misaligned interests and the relative importance of local and central government knowledge affects the optimal choice of policy-decision schemes. The empirical analysis shows that countries ́choices depend on the relative importance of their private information and the results differ significantly between unitary and federal countries.
Keywords: 1972-2010; Arbeitspapier; Graue Literatur